1990
DOI: 10.1148/radiology.177.3.2173843
|View full text |Cite
|
Sign up to set email alerts
|

Mixed form, diffusely scattered calcifications in breast cancer with apocrine features.

Abstract: Diffusely scattered calcifications visible with mammography are almost always benign. Certain patterns, however, should arouse concern. For example, extensive comedocarcinoma is associated with large areas of mammographically visible calcium deposition. The authors identified 10 women in whom calcifications were visible throughout large volumes of breast tissue at mammography. The calcifications did not resemble those typical of extensive comedocarcinoma, yet they were associated with extensive breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…7,8 Groups of calcification that can reflect a benign view may be seen in apocrine tumors. 9 Mammographic imaging revealed peripheral macrocalcifications with central cystic areas that filled the whole left breast in our case.…”
Section: Medical Pathologysupporting
confidence: 48%
“…7,8 Groups of calcification that can reflect a benign view may be seen in apocrine tumors. 9 Mammographic imaging revealed peripheral macrocalcifications with central cystic areas that filled the whole left breast in our case.…”
Section: Medical Pathologysupporting
confidence: 48%
“…Kopans et al . suggested in their study that, radiologically, these tumours might present distinctive characteristics, with a higher incidence of ‘mixed‐form’, diffusely‐scattered calcifications in tumours with apocrine features . However, Gilles et al .…”
Section: Discussionmentioning
confidence: 87%
“…Kopans et al suggested in their study that, radiologically, these tumours might present distinctive characteristics, with a higher incidence of 'mixed-form', diffusely-scattered calcifications in tumours with apocrine features. 7 However, Gilles et al studied 16 invasive apocrine carcinomas and showed that their mammographic presentation did not differ from other breast carcinomas. 8 Bilateral breast US and breast MRI were performed for the present case.…”
Section: Discussionmentioning
confidence: 99%
“…From the mammographies, the calcific debris was identified as milk of calcium and hence, escaped the benign cyst lumen during the sectioning, as well as the transfer to glass slides, and staining. Kopans et al (5) described 10 cases of typically benign calcifications associated with malignant cells, including milk of calcium layering in the dependent portion of cystically dilated acini lined with malignant cells. Even so, the classic crescent-shaped calcium precipitated in the cysts, and the spherical centrally lucent calcium deposits are almost always associated with the benign processes.…”
Section: Discussionmentioning
confidence: 99%